Micro-nano aeration oxygenation and column P gradient variations enhance the soil microbial environment, thereby increasing corn yield - Wang, Jiayue; Zhao, Yupeng; Fu, Yanbo; Wang, Zhiguo; Zhang, Wenlong; Zhu, Jinquan (Frontiers in Plant Science, 2026)
In field cultivation, crop yields are frequently limited by soil compaction and low fertilizer use efficiency. Regulating the rhizosphere microbial community structure of crops may represent an effective mitigation strategy. This study investigated the effects of micro-nano aeration oxygenation (WP) and Column P gradient levels on the microbial environment of maize rhizosphere soil and their impact on maize yield. Results demonstrate that WP significantly increased maize yield and biomass: under the medium Column P gradient (PM), the yield in the WP treatment increased from 1104.93 kg/hm² to 1387.04 kg/hm² compared to the control treatment (CP), representing a 25.56% increase (p<0.05). Soil and plant analyses further showed that, under identical Column P gradients, WP promoted more efficient absorption and utilization of available phosphorus than CP. Furthermore, by increasing soil oxygen content and improving aeration, WP enhanced enzyme activity and microbial diversity in the rhizosphere soil. Collectively, these findings indicate that combining micro-nano aeration oxygenation with appropriate phosphorus application can effectively stimulate rhizosphere microbial activity, thereby promoting maize growth and nutrient use efficiency. This approach offers a theoretical basis for optimizing irrigation and fertilization strategies in maize production systems.